Digital leader [ 5 simple keys to success and influence - Qualman, Erik (New York : McGraw-Hill, 2012)
Practical, profound, and a remarkably enjoyable read, Digital Leader is a 21st century manifesto for leveraging technology to become a better leader and help your employees, family, and friends reach their full potential
1. Life, leadership, legacy -- 2. Remove and improve -- 3. Complain = digital pain -- 4. Integrity and reputation : avoiding digital blunders -- 5. Simple = success -- 6. Who before what -- 7. Niche is the new norm -- 8. Personal is powerful -- 9. Be decisive -- 10. Fail forward, fail fast, fail better -- 11. Leverage inertia -- 12. Set laughable goals -- 13. Firm in destination- flexible in path -- 14. Recreate yourself -- 15. Connections = currency -- 16. Empower others -- 17. Digital hugs
Keywords: Influence (Psychology); Internet -- Social aspects; Leadership; Reputation